An NIR-II Responsive Nanoplatform for Cancer Photothermal and Oxidative Stress Therapy - Huang, Bin; Huang, Yuanpeng; Han, Han; Ge, Qiuyue; Yang, Dongliang; Hu, Yanling; Ding, Meng; Su, Yanqing; He, Yanbin; Shao, Jinjun; Chu, Jianfeng (Frontiers in Bioengineering and Biotechnology, 2021)
Chemodynamic therapy as an emerging therapeutic strategy has been implemented for oncotherapy. However, the reactive oxygen species can be counteracted by the exorbitant glutathione (GSH) produced by the tumor cells before exerting the antitumor effect. Herein, natural borneol (NB) serving as monoterpenoid sensitizer and copper sulphide (CuS NPs) as NIR-II photothermal agent were loaded in thermo-responsive vehicle (NB/CuS@PCM NPs). Under 1060 nm laser irradiation, the hyperthermia produced by CuS NPs can be used for photothermal therapy and melt the phase change material. In the acidity microenvironment, the CuS NPs released from NB/CuS@PCM NPs could degrade to Cu2+, then the Cu2+ was reduced to Cu+ during the depletion of GSH. As Fenton-like catalyst, the copper ion could convert hydrogen peroxide into hydroxyl radical for chemodynamic therapy. Moreover, the NB originated from NB/CuS@PCM NPs could increase the intracellular ROS content to improve the treatment outcome of chemodynamic therapy. The animal ex-perimental results indicated that the NB/CuS@PCM NPs could accumulate at the tumor site and exhibited an excellent antitumor effect. This work confirmed that the combination of oxidative stress-induced damage and photothermal therapy is a potential therapeutic strategy for cancer treatment.